Rewarding or aversive effects of buprenorphine/naloxone combination (Suboxone) depend on conditioning trial duration. (September 2014) - Canestrelli, Corinne; Marie, Nicolas; Noble, Florence
Abstract Buprenorphine is used as a sublingual medication in the treatment of opioid dependence. However, its misuse by i.v. injection may limit its acceptability and dissemination. A buprenorphine/naloxone (ratio 4:1) combination has been developed to reduce diversion and abuse. So far, the relevance of this combination has not been investigated in the animal models traditionally used to study the reinforcing effects of drugs of abuse. The aim of this study was to compare the rewarding effects, assessed by conditioned place preference (CPP), of buprenorphine and buprenorphine/naloxone combination following i.v. administration in mice. Animals were treated with different doses of buprenorphine or buprenorphine/naloxone combination (ratio 4:1), and CPP conditioning trial duration was 5 or 30 min. At the longest trial duration, a bell-shaped dose-response curve was obtained with buprenorphine, which was shifted significantly to the right with naloxone combination. At the shortest trial duration, an aversive effect was observed with the buprenorphine/naloxone combination in animals, involving opioid receptor-like 1 (ORL1). These findings may explain the discrepancies reported in the literature as some authors have shown a reduced buprenorphine/naloxone misuse compared to buprenorphine in opioid abusers, while others have not.